Work Hard, Play Hard: Gameboards and Merchants’ Way of Life in Middle Bronze Age Anatolia - Highcock, Nancy; Heffron, Yağmur (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
The study of gameboards in ancient West Asia has been revitalized by approaches foregrounding the social connections and new interactive spaces created by games such as Senet, Twenty-Squares, and Fifty-Eight-Holes. Often played between two people, these games can help explore the intimate rituals of social bonding and negotiation, particularly in diverse communities in which boundaries of class, gender, language, and geographic origins are continuously set, negotiated, and broken. Taking games as social lubricants (Crist, de Voogt and Dunn-Vaturi 2016) this paper will consider their role specifically within the diverse communities of the kārum network in Anatolia, where all extant boards are variants of the Game of Fifty-Eight-Holes. Egyptian in origin and prolific throughout ancient West Asia, the presence of boards used for Fifty-Eight-Holes at settlements within the kārum network is clearly associated with foreign presence. Integral to mercantile modes of being, gameboards represent a special category of material culture that carried a specific set of meanings and affordances and can therefore illuminate previously unconsidered dimensions of the encounters between Anatolians and Assyrians.